THE COMMERCIAL SPACES AND PRODUCTION OF URBAN SPACES SUPPLY MARKETS OF CUZCO - PERU - Gregorio de Andrade, Rita de Cassia [UNESP] (Univ Federal Espirito Santo, 2020)
The supply markets from Peru are resistance elements in cities that are becoming locus of new commercial spaces of the neoliberalism deployed over recent decades, such as shopping centers, hypermarkets and supermarkets. The aim of this paper is: 1) describe and analyze the supply markets of the Cuzco City, considering its location, profile of consumers and service goods they offer; and 2) understand the imbrication of these markets with the city and the relation to other commercial spaces, which can be competitive or complementary spaces. The research method was based on a literature review, analysis of documents and fieldwork, where were conducted observations, photographic mapping, semistructured interviews and application of questionnaires with the population. Finally, graphical and cartographical representations were created. The supply markets of Cuzco stand out in the production of the urban space, presenting a simultaneous relation of concurrence and complementarity with other commercial spaces. It was observed the relations of complementarity regarding the difference of content, products and services that are offered, consumers and the style of sociability. Apart from the recent changes in the style of life of the Cuzco citizens and the opening of modern commercial spaces, the supply markets are still being used as a place for food purchase, provision of services and meals such as breakfast and lunches. They are located in strategic points of the city, such as in the city center, ancient centers of the districts and close to important roads.
Keywords: Cuzco; commercial spaces; supply markets